Tuning structural stability and lithium-storage properties by d-orbital hybridization substitution in full tetrahedron Li2FeSiO4 nanocrystal. (February 2016) - Yang, Jinlong; Zheng, Jiaxin; Kang, Xiaochun; Teng, Gaofeng; Hu, Lin; Tan, Rui; Wang, Kai; Song, Xiaohe; Xu, Ming; Mu, Shichun; Pan, Feng
Abstract: Full tetrahedron connected structures possess considerable potential as cathodes for lithium-ion batteries (LIBs) due to more lithium storage sites to obtain high specific capacity. However, different from the full octahedron and octahedron/tetrahedron hybrid structures with coplanar or collinear, the tetrahedron network is connected by common vertex, which provokes structural instability and poor electrochemistry performance. Here, using first principles calculations combined with experiments, we found that a heavy distortion and big volume expansion during delithiation for full tetrahedron (LiO4, FeO4 and SiO4 tetrahedra) Li2 FeSiO4 nanocrystal lead to phase change or even structure fracture, and the optimized Ti(IV) doped in Fe sites can enhance the coupling effect among the tetrahedra by the strong d -orbital hybridization and like "spring" to hold these tetrahedra and prohibit structure fracture. Meanwhile, the Ti(IV) doping can also shorten the distance of two adjacent Li sites to decrease the activation barrier for Li-ion diffusion. Furthermore, the n-type doping effect increases the electronic conductivity. This discovery can be extended to other tetrahedron structures as well, providing a general approach to develop promising next-generation cathode materials for high-energy and long-life lithium-ion batteries. Highlights: We found heavy distortion during delithiated FeSiO4 lead to structure cracking. Ti(IV) doping enhanced the tetrahedral coupling by strong d -orbital hybridization. Ti(IV) doping increased Li-ion diffusion and electronic conductivity. This discovery provides a general approach to develop promising cathodes for LIBs.